Gastrointestinal Cancer Survival and Radiation Exposure among Atomic Bomb Survivors: The Life Span Study - Bockwoldt, Brandie; Sugiyama, Hiromi; Tsai, Kevin; Bhatti, Parveen; Brenner, Alina V.; Hu, Audrey; Kerr, Kathleen F.; Morenz, Eric; French, Benjamin; Phipps, Amanda I. (Cancer Epidemiology, Biomarkers & Prevention, 2021)
Radiation exposure is an established risk factor for the development of several forms of cancer, including gastrointestinal cancers. However, few studies have investigated the relationship between prediagnostic radiation exposure and survival after cancer diagnosis. Participants in the Life Span Study (LSS) of atomic bomb survivors who were diagnosed with a first primary invasive stomach, colon, or rectal cancer between 1958 and 2009 were followed for mortality during 1958-2014. Cox regression models were used to calculate HRs and 95% confidence intervals (CI) for associations of radiation dose from atomic bomb exposure with survival (cancer-specific and overall) after cancer diagnosis. Analyses were adjusted for city of primary exposure, sex, age at diagnosis, and year of diagnosis. We identified 7,728 eligible patients with cancer for analysis. We observed no statistically significant associations between radiation dose and cancer-specific survival among LSS participants with a gastrointestinal cancer. Higher radiation doses (≥1 Gy) were suggestively, but not significantly, associated with modestly poorer cancer-specific survival for colon cancer only (HR, 1.38; 95% CI, 0.90-2.12), and were associated with poorer overall survival regardless of cancer site. Although radiation exposure is associated with increased risk of gastrointestinal cancer incidence and mortality, study results are inconclusive about an association between prediagnostic radiation exposure and survival after gastrointestinal cancer diagnosis. Radiation exposure from the atomic bomb before gastrointestinal cancer diagnosis was not associated with cancer survival, but should be evaluated in relation to survival for other cancer types.